2010
DOI: 10.1007/bf03324937
|View full text |Cite
|
Sign up to set email alerts
|

A multi-dimensional questionnaire quantifying quality of life in elderly osteoporotic women: the Italian Triple-Q Osteoporosis Study

Abstract: The questionnaire intercepted the influence of osteoporosis on the quality of life of elderly women with vertebral fractures. Subjects who suffered from severe pain and were more fearful of falling were most likely to be severely osteoporotic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Using the fall experience in older adults as an opportunity to increase knowledge about osteoporosis, and particularly about the behaviors that can help decrease the risk and progression of osteoporosis and risk of falling should be considered. Conversely, as has been noted in prior research (Arnold, Busch, Schachter, Harrison, & Olszynski, 2005;Maggio et al, 2010), having a diagnosis of osteoporosis was associated with greater fear of falling. It is likely that those who knew they had osteoporosis feared a fracture with any fall, thus exacerbating their fear.…”
Section: Discussionsupporting
confidence: 47%
“…Using the fall experience in older adults as an opportunity to increase knowledge about osteoporosis, and particularly about the behaviors that can help decrease the risk and progression of osteoporosis and risk of falling should be considered. Conversely, as has been noted in prior research (Arnold, Busch, Schachter, Harrison, & Olszynski, 2005;Maggio et al, 2010), having a diagnosis of osteoporosis was associated with greater fear of falling. It is likely that those who knew they had osteoporosis feared a fracture with any fall, thus exacerbating their fear.…”
Section: Discussionsupporting
confidence: 47%
“…Additionally, the diagnosis of a chronic condition may impact upon HRQoL [15]. However, studies in relation to osteoporosis and fracture do not always specify when HRQoL data are measured [16].…”
Section: Introductionmentioning
confidence: 99%
“…From the clinical viewpoint, previous studies reported that physical inactivity can increase depressive symptoms and a significant association between physical inactivity and major non-communicable diseases, such as coronary heart disease, type 2 diabetes, breast cancers and colon cancers, which can also shorten life expectancy (15,16). There were several risk factors for falls in older adults has been recognised (17)(18)(19)(20)(21)(22)(23)(24)(25). However, no study has assessed the relationship between the storey on which elderly people live on and other fall-related variables such as fall risks and level of worry about falls.…”
Section: Discussionmentioning
confidence: 99%